The last fish tale : the fate of the Atlantic and survival in Gloucester, America's oldest fishing port and most original town - Kurlansky, Mark (2008)
From the "New York Times"-bestselling author of "Cod, Salt," and "The Big Oyster" comes the colorful story of a way of life that for hundreds of years has defined much of America's coastlines but is slowly disappearing.
Includes bibliographical references (pages [247]-253) and index.
Keywords: Fisheries -- Massachusetts -- Gloucester -- History -- Anecdotes; Fishing ports -- Massachusetts -- Gloucester -- History -- Anecdotes; Gloucester (Mass.) -- History -- Anecdotes